Uganda Note : Levels and Efficiency of Spending for Education - Wodon, Quentin; Ninan, Elizabeth; Mulindwa, Innocent; Rakotomalala, Mamy; Tsimpo, Clarence (Washington, DC: World Bank, 2017)
Due to population growth and gains in educationattainment, the size of Uganda’s education system isexpected to grow dramatically in the next dozen years inUganda. This will create pressure on scarce budgetresources. In order to accommodate larger cohorts ofstudents and provide an education of quality, gains ininternal efficiency will have to be achieved, but in additionsubstantial additional funding will also be needed.This note discusses issues related to the level andefficiency of spending for education in Uganda. After abrief review of recent enrollment trends and levels ofeducation attainment in the country, data on both publicand private spending for education are provided. One keyfinding is public spending for education has not kept pacewith enrollment. In part as a result, households currentlyshoulder almost two thirds of public and private educationspending in the country. Potential future trends in studentenrollment as well as budget implications are alsodiscussed, suggesting that education spending as a shareof GDP may need to increase substantially to achieveuniversal upper secondary completion